2014
DOI: 10.1177/2331216514545406
|View full text |Cite
|
Sign up to set email alerts
|

Gated Auditory Speech Perception in Elderly Hearing Aid Users and Elderly Normal-Hearing Individuals: Effects of Hearing Impairment and Cognitive Capacity

Abstract: This study compared elderly hearing aid (EHA) users and elderly normal-hearing (ENH) individuals on identification of auditory speech stimuli (consonants, words, and final word in sentences) that were different when considering their linguistic properties. We measured the accuracy with which the target speech stimuli were identified, as well as the isolation points (IPs: the shortest duration, from onset, required to correctly identify the speech target). The relationships between working memory capacity, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
59
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(68 citation statements)
references
References 44 publications
7
59
2
Order By: Relevance
“…Thus, in cases in which targets were highly predictable based on the sentence context, there was no penalty or advantage of age. Consistent with previous findings (Craig et al, 1993; Moradi, Lidestam, Hällgren, & Rönnberg, 2014; Moradi, Lidestam, Saremi, & Rönnberg, 2014), we found that word predictability tended to assist subjects in the early sensory perception of time-gated HC words but that older adults’ increased language experience did not facilitate higher performance in the TGW-recognition paradigm.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Thus, in cases in which targets were highly predictable based on the sentence context, there was no penalty or advantage of age. Consistent with previous findings (Craig et al, 1993; Moradi, Lidestam, Hällgren, & Rönnberg, 2014; Moradi, Lidestam, Saremi, & Rönnberg, 2014), we found that word predictability tended to assist subjects in the early sensory perception of time-gated HC words but that older adults’ increased language experience did not facilitate higher performance in the TGW-recognition paradigm.…”
Section: Discussionsupporting
confidence: 90%
“…A handful of recent studies have employed the gating paradigm to investigate identification of initial consonants, isolated words, and final words in low- and high-predictability sentences in older hearing aid users or older listeners with nominally normal hearing (pure-tone average or PTA ∼18 dB HL; Moradi, Lidestam, Hällgren, & Rönnberg, 2014) and young listeners (thresholds not provided) in quiet and noise (Moradi, Lidestam, & Rönnberg, 2013; Moradi, Lidestam, Saremi, & Rönnberg, 2014). The results demonstrated longer IPs in noise for the younger listeners and for the older hearing aid users in the low-predictability sentences compared with the older listeners with normal hearing.…”
mentioning
confidence: 99%
“…Ideally, HA fitting should take into account: (a) a range of personal and real life behavioural, physiological and other auditory related data; and (b) an analysis of the circumstances which are challenging for individual HA users on a continuous basis. It should also be appropriately supported by individualised rehabilitation treatments such as auditory training [12], as HA users depend more on their cognitive resources than normal hearing listeners in order to understand speech [13]. Nevertheless, evidence on how to link such information with appropriate, individualised management strategies is still lacking.…”
Section: B Challenges In Hl Managementmentioning
confidence: 99%
“…This effect has been shown on both young and adult listeners with HL (Arlinger, 2003;Hicks & Tharpe, 2002;Tun, McCoy, & Wingfield, 2009). In addition, several studies have shown that hearing aids do not fully restore speech difficulties of individuals with HL (e.g., Dimitrijevic et al, 2004;Moradi, Lidestam, Hällgren, & Rönnberg, 2014;Nakeva von Mentzer, 2014), which made perceiving speech stimuli cognitively demanding (Moradi et al, 2014;Rönnberg et al, 2013).…”
Section: Cognitive Consequences Of Hlmentioning
confidence: 99%
“…Moradi et al, 2014;Rönnberg et al, 2013) and could lead to decreased attention. Also, studying the effect of reducing cognitive fatigue on traffic safety can add to the understanding of the problem.…”
Section: Suggestions For Future Researchmentioning
confidence: 99%